Cancer Awareness and its Predictors among the Rural Population of Eastern India: A Cross-sectional Study - Dinesh Prasad Sahu; Sonu H. Subba; Prajna Paramita Giri (Indian Journal of Community Medicine)
Background: The global burden of cancer is increasing rapidly. In India, particularly, there is a low level of health awareness and significant information asymmetry. Improving awareness among the general population will bring about better health-seeking behavior and acceptance of screening methods. The study aims to assess the different aspects of cancer awareness and its determinants among the rural population. Methods: A cross-sectional study was conducted between August 2017 to August 2018. Data was collected from 1116 participants using a semistructured questionnaire. Information was collected on awareness about different cancers, sources of information, treatability, preventability, and risk factors of cancer. Data collected were analyzed using Statistical Package for Social Sciences (SPSS) version 22 (Armonk, NY, IBM Corp.). The level of awareness was presented as a percentage and the Odds ratio was calculated to find out the association between level of awareness and different sociodemographic characteristics. Results: 73.5% of the study participants had heard of cancer. Oral cancer was the most common cancer known to the study participants. Television was the most common source of cancer information. Knowledge about the preventability, treatability, and risk factors of cancer was very low. Tobacco was the most common risk factor identified. Awareness of cancer was found to be significantly associated with educational status. Conclusion: Awareness about general cancers was high, but awareness about specific cancers was low. There is a need to re-look at the health education campaigns about cancer to improve awareness of the rural population. Television and the Internet should be used as an effective medium to generate awareness about cancer.